ANALYSIS OF STUDENTS' SCIENCE LITERACY ON BUFFER SOLUTION MATERIAL IN PUBLIC HIGH SCHOOL 2 MUARA BADAK - Erika, Farah; Siswati, Julia; Widiyowati, Iis Intan; Hartati, Yuli (JCER (Journal of Chemistry Education Research), 2025)
Scientific literacy can be understood as students’ capacity to apply scientific knowledge, recognize problems, and formulate conclusions based on evidence. This study was conducted to examine the level of scientific literacy among students at SMA Negeri 2 Muara Badak. A descriptive quantitative research design was selected because the purpose was to portray a single variable independently without linking it to other variables. The research population comprised all eleventh-grade science students at SMA Negeri 2 Muara Badak. Using a saturated sampling technique, all students from three classes XI IPA 1, XI IPA 2, and XI IPA 3, were included, totaling 77 participants. Data were gathered through literacy test instruments as well as non-test methods, including observation sheets, student response questionnaires, and interviews. The results indicated that students’ scientific literacy was still within the moderate category, with an achievement percentage of 67.45%. Several factors contributed to this outcome, such as students’ limited reading habits related to science, their relatively weak comprehension of subject matter, and instructional processes that tended to be teacher-centered rather than promoting independent inquiry and conceptual engagement.